1988
DOI: 10.1246/bcsj.61.3569
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Fatigue Resistances and Thermal Stabilities of Heterocyclic Fulgides in PMMA Film

Abstract: Thermal stabilities of the colored forms at 80°C and photochemical fatigue resistances against coloration–discoloration cycles were measured in PMMA thin film, using 14 derivatives of fulgide with different heterocyclic structures. The indolyl (12), oxazolyl (13), and thiazolyl (14) derivatives showed very low thermal degradabilities (TD≤1.5%/day) while 12 and pyrazolyl derivative (9) showed low photochemical fatigues (PF≤0.2%/cycle), as compared with the furyl (1), thienyl (2), and pyrrolyl (3) derivatives. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 3 publications
0
35
0
Order By: Relevance
“…They possess photochemical characteristics valuable in practice, such as thermal irreversibility and high chemical stability, which enables these compounds to be considered as components for constructing molecular switches, and also systems of recording, storage, and treatment of information [1][2][3][4][5].…”
mentioning
confidence: 99%
“…They possess photochemical characteristics valuable in practice, such as thermal irreversibility and high chemical stability, which enables these compounds to be considered as components for constructing molecular switches, and also systems of recording, storage, and treatment of information [1][2][3][4][5].…”
mentioning
confidence: 99%
“…20,21 Therefore, fulgimides, as the most important fulgide derivatives, were synthesized to improve the hydrolytic stability by replacing the succinic anhydride ring with a succinimide ring (Scheme 3). In general, fulgimides, which have similar photochromic properties with the corresponding fulgides, exhibit hypsochromic shift in UV-Vis absorption spectra relative to the fulgides.…”
Section: Fulgide and Fulgimidesmentioning
confidence: 99%
“…34 Contrary to the high thermal stability in aprotic solvents, fulgides show rapid degradation in aqueous solution because the succinate anhydride ring can be easily hydrolyzed to a half-ester. 20,21 By replacing the succinate anhydride ring with a succinimide ring, fulgimides exhibit enhanced hydrolytic stability. 20,34 However, a previous study found that C-form …”
Section: Hydrolytic Stability Of Indolylfulgimidesmentioning
confidence: 99%
“…2 Indolylfulgides were synthesized and attracted particular research interest because of their promising photochromic properties, such as increased thermal stability, enhanced fatigue resistance, and visible wavelength absorption. 59,60 Subsequent studies reported several indolylfulgides with various substituents on the indole ring and bridging carbon. 58,[61][62][63] Recently, Yokoyama et al reported a trifluoromethyl substituted indolylfulgide which demonstrated the most promising photochromic properties.…”
Section: Fulgidesmentioning
confidence: 99%
“…15 Although fulgides display promising photochromic properties, the succinic anhydride ring causes rapid solvolytic degradation in protic solvents or aqueous media. 59,71 Fulgimides improve the hydrolytic stability of fulgides by replacing the succinic anhydride ring with a succinimide ring and retain the promising photochromic properties. Hydrolytic stability is crucial for applications in biological systems and humid environments.…”
Section: Introductionmentioning
confidence: 99%